2014
DOI: 10.1007/s00125-014-3316-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vitamin D deficiency during pregnancy results in insulin resistance in rat offspring, which is associated with inflammation and Iκbα methylation

Abstract: Maternal vitamin D deficiency during pregnancy results in insulin resistance in the offspring, which is associated with persistently increased inflammation. Persistently decreased Iκbα expression, potentially caused by changes in Iκbα methylation, plays an important role in persistent inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 33 publications
2
55
0
Order By: Relevance
“…Moreover, NFKB inhibitor-a (NFKBIA) (also known as hepatic IjBa) is increased by RV. This gene plays an important role in persistent inflammation, and its decrease is associated with 25(OH)-VitD3 deficiency [33]. Conversely, retinoid X receptor b (RXRB), which forms a complex with the VitD receptor (VDR) and would be necessary to activate VDR targets [34], is decreased in the PBMCs of control children by RV.…”
Section: Gene Arrays From In-vitro Rv-infected Pbmcs From Preschool Cmentioning
confidence: 99%
“…Moreover, NFKB inhibitor-a (NFKBIA) (also known as hepatic IjBa) is increased by RV. This gene plays an important role in persistent inflammation, and its decrease is associated with 25(OH)-VitD3 deficiency [33]. Conversely, retinoid X receptor b (RXRB), which forms a complex with the VitD receptor (VDR) and would be necessary to activate VDR targets [34], is decreased in the PBMCs of control children by RV.…”
Section: Gene Arrays From In-vitro Rv-infected Pbmcs From Preschool Cmentioning
confidence: 99%
“…Studies in rats have revealed that vitamin D deficiency in pregnant dams affects insulin action in the offspring, and this is thought to occur via methylation of the gene encoding nuclear factor κB inhibitor α 50 . Other animal studies have shown that periconceptional supplementation (or deprivation) of choline, folic acid, methionine, or vitamin B 12 can affect the DNA methylation patterns and phenotype of the offspring 51 .…”
Section: Consequences Of Gestational Diabetes For Offspringmentioning
confidence: 99%
“…Different micronutrient deficiencies such as folate, vitamin A, vitamin B, potassium, iron, and selenium correlated with hypermethylation of tumor suppressor genes, demonstrating a role in cancer [78,79]. Deprivations of vitamin D [80], calcium [81], magnesium [82], and chromium [49] could increase the risk of developing T2DM through promoting aberrant methylation patterns in genes involved in glucose homeostasis, insulin signaling and inflammatory response. Additionally, deficits of selenium [50] and vitamin A were associated with the pathogenesis of CVD by affecting the DNA methylation status of critical genes [52].…”
Section: Diet and Epigenetic Signaturesmentioning
confidence: 99%